Evaluating water pollution characteristics based on Lagrangian approach - Arkhipov, B. V; Solbakov, V. V; Solov’ev, M. B; Shapochkin, D. A (Water resources, 2015)
A method is proposed for calculating water pollution characteristics. A correct definition and evaluation of those characteristics is shown to be possible only with the use of Lagrangian approach. To overcome the difficulties in calculations on a Lagrangian grid subject to deformations, specific features of interpolating the estimated values in the passage from deformed Lagrangian grid to an undeformed grid are considered. A new procedure is proposed, which preserves the values of major functionals at such interpolation. The character of perturbations of estimates, arising from the restructuring of the grid and the subsequent interpolation, is analyzed. Those perturbations are shown to be insignificant.